The geometry of type : the anatomy of 100 essential typefaces. - Coles, Stephen; Spiekermann, Erik (London : Thames & Hudson, 2012)
This book explores 100 traditional and modern typefaces in loving detail, with a full spread devoted to each entry. Characters from each typeface are enlarged and annotated to reveal key features, anatomical details, and the finer, often-overlooked elements of type design, which shows how these attributes affect mood and readability. Sidebar information lists the designer and foundry, the year of release and the different weights and styles available, while feature boxes explain the origins and best uses for each typeface, such as whether it is suitable for running text or as a display font for headlines. To help the reader spot each typeface in the wider world, the full character set is shown, and the best letters for identification are highlighted. This beautiful and highly practical work of reference for font spotters, designers and users is a close-up celebration of typefaces and great type design.
boek